Review of simulation-based life cycle assessment in manufacturing industry. Issue 1 (1st January 2019) - Liu, Yu; Syberfeldt, Anna; Strand, Mattias
ABSTRACT: The manufacturing industry has a duty to minimize its environmental impact, and an increasing body of legislation mandates environmental impact evaluations from a life cycle perspective to prevent burden shift. The manufacturing industry is increasing its use of computer-based simulations to optimize production processes. In recent years, several published studies have combined simulations with life cycle assessments (LCAs) to evaluate and minimize the environmental impact of production activities. Still, current knowledge of simulations conducted for LCAs is rather disjointed. This paper accordingly reviews the literature covering simulation-based LCAs of production processes. The results of the review and cross-comparison of papers are structured in terms of seven elements in line with the ISO standard definition of LCA and report the strengths and limitations of the reviewed studies.